Delivery of highly proliferative co-cultured skin cells in 3D GelMA core-shell microspheres: in vitro studies - Tan, Pei Leng (Nanyang Technological University, 2022)
Burns continues to pose as a global public health problem that results in significant health, social and economic consequences. Severe burns lead to about 180,000 deaths worldwide annually and millions of patients suffer from non-fatal burns that result in substantial and life-long physical and psychological morbidities. Split-thickness autografting remains the gold standard in the management of burn wounds to date. However, the use of this method is greatly challenged in patients with extensive burn wounds where healthy donor sites are scarce for skin graft harvesting, resulting in a delay in wound closure, detrimental wound infection, scarring and even death. The cornerstone in improving a patient’s likelihood of survival, therefore, lies in the efficacy of the treatment to enhance the re-epithelization of skin to restore its barrier function. This has led to the emergence of different cell-based treatments for large burn wounds, from the first-generation cultured epithelial autografts (CEA) to the next generation of autologous cell-suspension delivery. In light of the limitations of the CEA sheet and cell suspension spray, the next generation of cell-based therapy could be through the delivery of encapsulated proliferative skin cells that could cover a large area and for the restoration of functional epidermis and dermis in the injured skin. This dissertation thus entails the scalable delivery of highly proliferative co-cultured skin cells in 3D GelMA core-shell microspheres for efficient re-epithelization of an extensive burn wound. In pursuance of achieving monodisperse core-shell microspheres for more uniform cell encapsulation and delivery, the nexus between the inherent GelMA properties and electrospraying parameters on the fabrication of GelMA core-shell microspheres was first investigated. Through the study, uniform 3D GelMA core-shell microspheres with an average diameter of 382μm ± 26μm were successfully achieved when electro-sprayed under the following optimal conditions: a concentration of 10% GelMA-DS40 and 10% GelMA-DS90/0.5% alginate that can support cell growth were used as the core and shell solutions and infused through a 21G-16G co-axial nozzle at a total flow rate of 15 mL/hr. Upon spraying, the microspheres were then collected in a 100mM BaCl2 collector bath. To emulate the epidermal-mesenchymal interactions in a full-thickness skin equivalent, primary neonatal human dermal fibroblasts (HDFs) and hTERT-immortalized primary neonatal human keratinocytes (kerCTs) were encapsulated at a 1:5 ratio. An optimal concentration of 4 million cells/mL of HDFs-laden GelMA solution and 20 million cells/mL of kerCTs-laden GelMA-alginate solution were then sprayed as core-shell solution respectively under the optimal electro-spraying parameters. Both HDFs and kerCTs were successfully encapsulated in the core and shell compartment of 3D GelMA core-shell microspheres in a facile manner. The growth and viability of the encapsulated skin cells in 3D GelMA core-shell microspheres were subsequently evaluated through quantitative and qualitative means. An in-vitro 7-days cell study highlighted that the porous RGD-containing GelMA core-shell microspheres were able to support the growth of encapsulated HDFs-kerCTs in their respective core-shell compartment with a high cell viability of 74% post-encapsulation. This, however, only holds true at the early stage of co-culture where there is available substrate space for the encapsulated cells to attach and proliferate. At the later stage when the cells have proliferated till confluency, the effect of contact inhibition (of proliferation) and severe competition for oxygen take precedence over the provision of the cell-favourable microenvironment, leading to an abated cell viability of 44%. It was then proven that the co-culture of keratinocytes with fibroblasts in GelMA core-shell microspheres significantly enhanced the proliferation of keratinocytes as compared to monocultured keratinocytes, owing to a double paracrine signalling pathway well-established by many studies. Co-culturing kerCTs with HDFs also expedited the time in which the proliferation of kerCTs was significantly enhanced, as compared to mono-cultured kerCTs which is crucial in clinical settings where time is of the essence. An in-vitro 14-days study then demonstrated the capability of skin-cell laden GelMA core-shell microspheres to degrade and co-deliver both kerCTs and HDFs. The delivered skin cells were able to attach and expand into a large epithelial and dermal sheet with their proliferative capacity retained even after 14 days of co-culture, highlighting its potential to expand into a functional skin construct for large burn wound healing. The scalability of co-axial electrospraying 3D GelMA core-shell microspheres was then confirmed, where a high yield of core-shell microspheres that can cover 70% of a 90mm petri dish was successfully achieved in just 3 minutes of fabrication time. In retrospect, the experimental findings successfully proved that compartmentalized human keratinocytes and fibroblasts in 3D GelMA core-shell microspheres were able to support the proliferation of co-cultured keratinocytes for a scalable facile co-delivery of skin cells to extensive burn wounds.